Effects of gamma oryzanol supplimentation of lipid profile, anabolic/ catabolic hormones, circulating binding proteins and anthropometric changes in young males during resistance training - Eslami, Saghar (2012)
Resistance training is an element of conditioning and training for almost any sports. Speeded muscle strength increments are seen whenever resistance exercise is joined by the consumption of nutritional supplements. Although, there are very limited researches about the efficacy of gamma oryzanol supplementation with resistance exercise in humans, the usage of gamma oryzanol in strength athletes is prevalent. The aim of this single blind, placebo-controlled, randomized intervention trial is to determine the effects of dietary 600 mg/day gamma oryzanol supplementation during a 9-week resistance training program on altering lipid profile, anabolic/catabolic hormones, circulating binding proteins and anthropometric measures of young males during resistance training. Thirty two eligible males with no continuous resistance training experience during six months before the study participation, with age 18-24 years were selected for the study. They were randomized into two groups (either 600 mg of gamma oryzanol or lactose in the form of capsules). Prior to the study commencement, subjects’ one Repetition Maximum (1-RM) was determined by means of 1-RM strength tests on the regular leg curl and bench press machine, which was repeated on the last day of study. On the commencement day and the last day of the study, they were examined for anthropometric and body measurements. Supervised resistance training was performed four times a week, performing three sets (consisting of 6–12 repetitions) per exercise with three minutes rest, for a period of 9 weeks for each participant,accompanied with the consumption of supplement. At the study commencement in two times, before and after the acute resistance exercise, and at the end of the 9-week and 24 hours after the last resistance exercise performance, blood sampling were taken following 10-12 hour fast. Independent sample t-test and general linear model were applied to compare within and between group differences in mean scores. In terms of analyzing hormonal changes and blood protein levels over 4 time points of sampling, data were analyzed with 2×4 (Group × Time points) repeated measures analysis of variance. Bonferroni corrected post hoc test was used for analyzing difference of changes between time points. All testing of hypotheses were two-tailed,with significant judgment by 95% confidence interval and p<0.05. There was no significant difference between the baseline characteristics and the target variables at baseline. In terms of anthropometric changes, there was no significant change between the supplement and placebo groups after the 9-week intervention. On the other hand, 1-RM of bench press (p<0.001) and leg curl (p=0.005), which are markers of muscle strength increased after gamma oryzanol supplementation in the supplement group compared with placebo group. Among markers of blood lipid profile, very low-density lipoprotein (VLDL-C) (p=0.034) and triglyceride (TG) (p=0.027) levels declined in the supplement group greater than the placebo group after the 9-week supplementation which shows the effect of gamma oryzanol supplementation on decreasing these markers, but no difference has been shown for high-density lipoprotein (HDL-C), low-density lipoprotein (LDL-C) and total cholesterol (TC) (p>0.05). In terms of serum mineral concentration, there was only significant difference between the supplement and placebo groups for zinc concentration after the 9-week intervention. During the study, it has been observed that gamma oryzanol affected on total testosterone (p=0.041), cortisol (p=0.010) and growth hormone (GH) (p=0.047) levels, unlike free testosterone, triiodothyronine (T3), thyroxine (T4), thyroidstimulating hormone (TSH), insulin-like growth factor-I (IGF-I), estradiol, dehydroepiandrosterone sulfate (DHEAS), sex hormone-binding globulin (SHBG),epinephrine, norepinephrine and insulin-like growth factor-binding protein 3 (IGFBP3) (p>0.05). Moreover, testosterone to cortisol ratio significantly changed (p<0.001) in the supplement group compared with the placebo group; however, no significant change was shown for total testosterone to SHBG ratio (p>0.05) between the supplement and placebo groups. In conclusion, the current study demonstrated that gamma oryzanol supplementation may benefit resistance athletes to improve anabolic markers as well as increasing muscle strength. However, this supplement could not improve all markers of interest and more researches need to be carried out for understanding the mechanism of effects and substitute this supplement with harmful hormonal drugs and supplements.